1998
DOI: 10.1037/1064-1297.6.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic temporal discounting in social drinkers and problem drinkers.

Abstract: Two studies compared participants, distinguished by their typical alcohol consumption, on the degree to which they discounted the value of delayed, hypothetical amounts of money. Heavy social drinkers in Study 1 and problem drinkers in Study 2 both showed greater temporal discounting than light social drinkers; this difference was stronger in Study 2. Both studies found that a hyperbolic function described temporal discounting more accurately than an exponential function. These results are consistent with exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
431
5
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(475 citation statements)
references
References 54 publications
31
431
5
8
Order By: Relevance
“…Consistent with previous findings (Vuchinich and Simpson, 1998;Petry, 2001;Mitchell et al, 2005b), the AA group made impulsive choices significantly more often than the CS group (F 1,16 ¼ 5.846, p ¼ 0.028). Also, consistent with our previous findings (Mitchell et al, 2005b), ICR was sensitive to both the later reward delay (Figure 2c; F 1.74,27.83 ¼ 12.35; po0.001) and the later reward amount (Figure 2d; F Figure 2d).…”
Section: Acute Ntx Does Not Reduce Impulsive Choice In Either Groupsupporting
confidence: 91%
“…Consistent with previous findings (Vuchinich and Simpson, 1998;Petry, 2001;Mitchell et al, 2005b), the AA group made impulsive choices significantly more often than the CS group (F 1,16 ¼ 5.846, p ¼ 0.028). Also, consistent with our previous findings (Mitchell et al, 2005b), ICR was sensitive to both the later reward delay (Figure 2c; F 1.74,27.83 ¼ 12.35; po0.001) and the later reward amount (Figure 2d; F Figure 2d).…”
Section: Acute Ntx Does Not Reduce Impulsive Choice In Either Groupsupporting
confidence: 91%
“…(1999) showed that substance abusers discounted delayed outcomes at greater rates than non-abusers. Similar findings have been reported with abusers of nicotine (Bickel et al, 1999), opioids (Madden et al, 1997), and alcohol (Petry, 2001;Vuchinich and Simpson, 1998). Despite the fact that a correlation between drug abuse (and other behaviors often characterized as impulsive) and delay discounting has been demonstrated, it is not clear whether increased delay discounting underlies drug abuse and other disorders or if long-term exposure to drugs or other variables underlie increased delay discounting.…”
Section: Introductionsupporting
confidence: 55%
“…Kirby, Petry, and Bickel (1999) replicated this finding using delayed monetary rewards that participants had a chance of actually receiving. In addition, Vuchinich and Simpson (1998) studied college students and found that both heavy social drinkers (Experiment 1) and problem drinkers (Experiment 2) showed greater temporal discounting of hypothetical monetary rewards than light social drinkers. Petry and Casarella (1999) suggested that some of the factors that determine group membership may have additive effects on discounting.…”
Section: Applications To Group Differencesmentioning
confidence: 99%